Design of Calixarene‐Based ICD Inducer for Efficient Cancer Immunotherapy - Zhang, Zhanzhan; Yue, Yu‐Xin; Li, Qiushi; Wang, Ying; Wu, Xueyao; Li, Xue; Li, Hua‐Bin; Shi, Linqi; Guo, Dong‐Sheng; Liu, Yang (Advanced functional materials, 2023)
Immunogenic cell death (ICD), which in situ generates cancer vaccines and elicits protective cognate anticancer immunity, has brought brightness to cancer immunotherapy. However, poor immunogenicity and low response rate of current ICD‐inducing strategies restrict the development and clinical application of ICD‐based immunotherapy. Herein, a novel calixarene, quaternary ammonium‐modified azocalix[4]arene (CA‐3) that drive bona fide ICD with high efficiency, is presented. In addition, the unique macrocyclic structure offers CA‐3 with great potential to bind with anticancer drugs via host–guest interactions. With these two functions in one molecule, CA‐3 effectively cooperates with various chemotherapeutics to improve their anticancer performance by activating ICD‐associated anti‐tumor immunity. These unique characteristics make CA‐3, a general platform for improving the prognosis of many chemotherapies commonly used in clinical practice. Furthermore, the structure‐activity relationship established in this study also provides insights for the design and synthesis of more efficient calixarene‐based ICD inducers. A novel calixarene, CA‐3 that can drive bona fide immunogenic cell death (ICD) and deliver chemotherapeutics to tumors is presented in this study. These two functions ensure that CA‐3 cooperates with chemotherapeutics to improve anticancer performance by activating ICD‐associated anti‐tumor immunity. This bifunctional calixarene provides a general platform for improving the prognosis of many chemotherapies commonly used in clinical practice.